(3GdGYJHGQGJ GdfXQjI aj GdCMcGe GdfLhejIs - (3CHh GdMSjf Ydj Hf YHO Gddg Hf eMeO Hf gjOhQ GdJGOdi GdaGSi,cGf MjG (B866 (3g`s
(3ChdgG (B:s
(3bGd GdMeO ddg eYWi GdLhO ai YGde GdhLhO hHYO , aGdZQV HgPG GdcJGH JdNjU eG ETJedJ Ydjg UfGYI fXQjI GdeYQaI eG EYJeOJg HGdJLQHI hHELeGY hSejJg HGdEYJHGQGJ GdfXQjI ai GdCMcGe GdfLhejI s
(3BNQgG (B:s
(3aEf cGf bhjkG eCNhPkG ef GdbQGfGJ hGdcShaGJ GdTeSjI OGe cKjQkG hEf cGf VYjakG eCNhPkG ef GdJMGhjd hGdELJeGYGJ OGe bdjdkG hGddg CYde cedJ s
(3Vef eLehY , JQJjHgG (B: (3ef U (B235 - (3U(B238s
(3HgG WeS hYOe hVhMs
(3HBNQgG ChQGb ajgG fbhd eNJdaI hLOGhd adcjIs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B306 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B141s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B2 s
Keywords: (3Gdadcs